MATERIAL DIDÁTICO DE MATEMÁTICA PARA EaD: Especificidades, Limitações e Necessidades - Leandro, Marcele Cristian Salvan Garcia (2011)
This research is the object of study of mathematics textbooks used for Distance Education (DE). This research was built having as theoretical studies on distance education and the teaching materials for distance education. The question that guides this study is defined as: what are the characteristics, needs and limitations inherent in the educational material focused on mathematics and Distance Education? Faced with this question, due the following objective: to explain the needs, limitations and specifics of Teaching Materials for Undergraduate courses in mathematics at a distance. This research was conducted in the city of Ponta Grossa / PR, with the fields of research, State University of Ponta Grossa (UEPG), characterized as a case study. In the investigation in question, this study referred to the description of the organization of the course textbook Instrumentation for the Teaching of Mathematics in Distance Education I UEPG, the activities of the platform MOODLE and files that complement the textbook, explaining what the specifics, limitations and needs of educational materials developed for distance education. As that investigation, the textbook analysis meets some needs inherent to a material written for this mode, but it shows with some limitations and resource constraints, compromising student learning. Use of MOODLE platform proved to be a necessity and an important tool for interaction and communication between teachers and students, allowing students a more active role in their education, more autonomy, promoting a more efficient construction of their learning and acquisition of their knowledge.